A Review of Current Bacterial Resistance to Antibiotics in Food Animals - Xu, Chunming; Kong, Lingqiang; Gao, Hanfang; Cheng, Xiyu; Wang, Xiumin (Frontiers in Microbiology, 2022)
The overuse of antibiotics in food animals has led to the development of bacterial resistance and the widespread of resistant bacteria in the world. Antibiotic-resistant bacteria (ARB) and antibiotic-resistant genes (ARGs) in food animals are currently considered emerging contaminants, which are a serious threat to public health globally. The current situation of ARB and ARGs from food animal farms, manure, and the wastewater was firstly covered in this review. Potential risks to public health were also highlighted, as well as strategies (including novel technologies, alternatives, and administration) to fight against bacterial resistance. This review can provide an avenue for further research, development, and application of novel antibacterial agents to reduce the adverse effects of antibiotic resistance in food animal farms.